Wuyi Rock Tea Drinking Associated Knowledge and Practice: A Case Study from the Anthropological Perspectives - Wang, Yanyu; Tian, Robert Guang (Journal of Knowledge Management Practice, 2024)
There are two domains in the anthropological knowledge of food and the practice of foodways: the materialist school, represented by Marvin Harris, and the teleological school, represented by Claude Levi Strauss. Scholars have considered these two schools irreconcilable for many years. This paper made a practical study of the two domains by investigating the consumption of Wuyi Rock Tea in Fujian Province from the perspective of anthropology. It suggests that Wuyi Rock Tea drinking has become a symbolic social behavior in Chinese society along with Chinese pragmatic principles. Consumers enjoy Wuyi Rock Tea and desire to consume it for various reasons.
Keywords: knowledge management; Wuyi Rock Tea; idealism-materialism; consumption pattern